2006
DOI: 10.1002/asi.20319
|View full text |Cite
|
Sign up to set email alerts
|

Query expansion behavior within a thesaurus‐enhanced search environment: A user‐centered evaluation

Abstract: The study reported here investigated the query expansion behavior of end-users interacting with a thesaurusenhanced search system on the Web. Two groups, namely academic staff and postgraduate students, were recruited into this study. Data were collected from 90 searches performed by 30 users using the OVID interface to the CAB abstracts database. Data-gathering techniques included questionnaires, screen capturing software, and interviews. The results presented here relate to issues of search-topic and search-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 67 publications
2
32
0
Order By: Relevance
“…Three types of query expansion are discussed in literature: manual, automatic, and interactive (i.e., semiautomatic, user-mediated, or user-assisted). In [7] is stated that thesauri have been recognized as a useful source for enhancing search-term selection for query formulation and expansion. In their study they mention that in 50% of the searches where additional terms were suggested from the thesaurus, users stated that they had not been aware of the terms at the beginning of the search.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Three types of query expansion are discussed in literature: manual, automatic, and interactive (i.e., semiautomatic, user-mediated, or user-assisted). In [7] is stated that thesauri have been recognized as a useful source for enhancing search-term selection for query formulation and expansion. In their study they mention that in 50% of the searches where additional terms were suggested from the thesaurus, users stated that they had not been aware of the terms at the beginning of the search.…”
Section: Related Workmentioning
confidence: 99%
“…Additionally, the user may get confused if the system retrieves documents that do not contain the original query terms. But, using a thesaurus gives the user confidence and security that her needs are met, as reported in [10], while in [7] is mentioned that narrower and related terms taken together constitute approximately 60% of the queryexpansion terms selected by users.…”
Section: Related Workmentioning
confidence: 99%
“…Wordnet (Miller 1995), thesaurus development (Jun 2006;Tseng 2002), query expansion (Efthimiadis 1996;Greenberg, 2001;Khan & Khor 2004), and thesaurus-based search (Shiri & Revie 2006) …”
Section: Three Traditional Information Organization Approachesmentioning
confidence: 99%
“…Query rewriting [3] are the stages of the process of information retrieval by user's initial query statement by adding enhanced search terms to improve information retrieval performance. Query rewriting can also be referred to as query expansion, which according to Hazra Imran et al [4] is the process of completing additional query term or phrase in the beginning as a way to improve the performance of information retrieval.…”
Section: Introductionmentioning
confidence: 99%
“…This is because search engines are not able to look for patterns of relevant documents or the user does not state when the search request with the correct information [1]. The lack of a search engine can be overcome by doing a query rewriting.Query rewriting [3] are the stages of the process of information retrieval by user's initial query statement by adding enhanced search terms to improve information retrieval performance. Query rewriting can also be referred to as query expansion, which according to Hazra Imran et al [4] is the process of completing additional query term or phrase in the beginning as a way to improve the performance of information retrieval.…”
mentioning
confidence: 99%